The Role of Different Matrixin Gene Expressions on Cerebral Bleeding among Patients with Deficiency of Coagulation Factor XIII: Cerebral hemorrhage and MMP-2,9 gene expression - Mao, Lei; Huang, Yiyang; Jia, Weiqiang; Zhou, Zhi; He, Xiaobo (Cellular and Molecular Biology, 2022)
Enzymes of the matrixin family could be seen as a critical determinant in the breakdown of the extracellular matrix, cell membrane, and tissue regeneration and are interned in the process of brain bleeding. On the other hand, coagulation factor XIII deficiency is a sporadic hemorrhagic disease with an estimated prevalence of 1 in 1-2 million people. Cerebral hemorrhage is the leading cause of death in these patients. This study investigated the relationship between the expression of matrix metalloproteinase 9 and 2 genes with cerebral hemorrhage in these patients. For this purpose, in this case-control study, by examining the clinical and general findings of the studied patients, the Q-Real-time RT-PCR method was used to quantitatively examine the mRNA levels of matrix metalloproteinase 9 and 2 in 42 patients with hereditary deficiency of coagulation factor XIII, including two groups with and without a history of cerebral hemorrhage (case and control groups, respectively). A comparative method (2-ΔΔCT) was used to check the expression level of the target genes. The GAPDH gene expression levels were used to standardize the expression of the measured matrix metalloproteinase genes. The results showed that bleeding from the umbilical cord was the most common clinical symptom among all patients. High levels of MMP-9 gene expression were observed in 13 patients of the case group (69.99%) and three patients of the control group (11.9%). which showed a significant difference (CI: 2.77-95.3, P=0.001) Patients with coagulation factor XIII deficiency show a wide range of clinical symptoms crucial in screening and diagnosing this group of patients. Based on the results of this study, it seems that the increased expression of the MMP-9 gene is due to polymorphism or inflammation related to the pathogenesis of cerebral hemorrhage in this category of patients. It may be conceivable to diminish this impact by utilizing MMP-9 inhibitors and offering assistance to diminishes these patients' hospitalization and passing rates.